Development and feasibility of an inter-agency physical activity and education programme for adults with multimorbidity in primary care: Activ8 - Aine Ryan; Susan M Smith; Vanda Cummins; Catriona Murphy; Rose Galvin (Journal of Multimorbidity and Comorbidity)
Background While physical activity is widely recommended for many long-term conditions, it may be difficult to achieve for patients managing multiple conditions. We aimed to determine the feasibility of an inter-agency exercise and education programme for patients with multimorbidity in primary care. Methods We conducted an uncontrolled pilot study with adults with multimorbidity, recruited in two community healthcare organisations in an urban area in Ireland. The six-week pilot intervention combined an individually tailored gym-based exercise programme and education to support self-management. Feasibility of the Activ8 programme was assessed using a mixed methods process evaluation. Outcome measures at baseline and at 6 weeks included recruitment and retention, gait speed, grip strength, quality of life and self-efficacy. Focus groups and interviews explored participants and facilitators’ perceptions of the programme. Results 19 participants with ≥2 chronic conditions were recruited over three-weeks with similar attrition at both sites (≤40%). Overall, the results indicate that Activ8 was feasible and acceptable to patients and practitioners. Quantitative outcome measures suggested improvements in most outcomes. Qualitative data analysis indicated that Activ8 addressed an overarching concept of patient-centeredness among participants. Three key themes included perceived personal programme impact, the personalised composition of the programme and the evolving nature of primary care practice. Conclusion While further definitive evidence is needed and attrition from the programme needs to be considered, the Activ8 Programme was acceptable to both patients and professionals in two different primary care areas with the potential for positive impacts for adults living with multimorbidity.